Detailed surgical description of porcine vascularized thymus lobe transplantation - Gunes, M. Esad; Fujiwara, Sho; Wolbrom, Daniel H.; Cadelina, Alexander; Qudus, Susan; Ekanayake-Alper, Dilrukshi; Hajosi, Dominik; Sachs, David H.; Nowak, Greg (Frontiers in Transplantation, 2024)
BackgroundDespite advances in immunosuppressive therapies, chronic rejection and immunosuppression-related complications remain significant challenges in transplantation. Developing transplantation tolerance through thymus transplantation may offer a solution. This paper details our technique for procuring and transplanting porcine vascularized thymic lobes (VTL), which can be utilized to study and research allogeneic and xenogeneic transplantation models in large animals.MethodsGalT-KO miniature swine (n = 16) and baboons (n = 12) were used for VTL transplantation. The right or left cervical thymic lobe was dissected, harvested with its artery and veins, and flushed with cold lactated Ringer's solution. VTL graft was transplanted intraabdominally in all animals.ResultsWe performed non-survival (n = 2) and survival (n = 2) VTL autotransplants in pigs and xeno-VTL and kidney transplants in baboons (n = 12). All grafts immediately turned pink after reperfusion and had good blood inflow and outflow. Pigs in the survival autotransplant group were euthanized immediately post-operatively due to complications related to VTL donation. One baboon lost its graft due to antibody-mediated rejection, and another lost it due to venous thrombosis. Other baboons had no complications and survived until the endpoint.ConclusionHere, we describe our approach and experience in swine vascularized thymic lobe procurement and transplantation. The technique requires moderate surgical skills to achieve reproducible results. Living-donor VTL donation in pigs is not recommended due to the high risk of surgical complications related to the harvesting procedure.